The Choosing : A Rabbi's Journey from Silent Nights to High Holy Days - Myers, Andrea (Book collections on Project MUSE., 2011)
In The Choosing, Andrea Myers fuses heartwarming anecdotes with rabbinic insights and humor to describe what it means to survive and flourish on your own terms. Portioned around the cycle of the Jewish year, with stories connected to each of the holidays, Myers draws on her unique path to the rabbinate-leaving behind her Christian upbringing, coming out as a lesbian, discovering Judaism in college, moving to Israel, converting, and returning to New York to become a rabbi, partner, and parent.